Analisis Pengelolaan Sampah di Pondok Pesantren Desa Tangkit Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Siahaan, Sondang; Erris, Erris; Rina, Rina; Supriatna, Supriatna (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze waste management in Islamic boarding schools in Tangkit Village, Sungai Gelam District, Muaro Jambi Regency. The type of research conducted is quantitative research with data collection methods using questionnaires and observations. The sample in this study was 6 Islamic Boarding Schools. The results of this study found that waste management in the Islamic Boarding School was still far from optimal.